Sensory Analysis of Fish Chili Sauce With The Addition Of Fermented Cob Fish (Auxis Thazard) - Ni Made Darmadi; Dewa Gede Semara Edi; I Wayan Sudiarta (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Fish Chili Sauce is a type of food as a side dish, which serves to arouse the appetite of consumers. By adding fermented tuna to the fish sauce, it is hoped that the fish sauce made will have a distinctive taste in Fermentation. The most essential microbes are Lactic Acid Bacteria. Lactate can improve the taste of the product and also lowers the pH of the substrate so that it can suppress the life of pathogenic microbes. The research method is the experimental method with 4 treatments and 3 replications. The results showed that the quality fish sauce formula was Treatment A (fish sauce with the addition of fermented tuna as much as 10%) with a value of 58.06% of water content, 78.92% of fat content, 1.43% of protein content, pH 5.12; TPC <25 cfu/g sample, Color Value is 6 (Preferred), Taste Value is 7 (Highly Favored), Texture Value of 7, and Appearance Value 7